Management of periocular keratinocyte carcinomas with Mohs micrographic surgery and predictors of complex reconstruction: a retrospective study - Dominga Peirano; Sebastián Vargas; Leonel Hidalgo; Francisca Donoso; Eugenia Abusleme; Felipe Sanhueza; Consuelo Cárdenas; Katherine Droppelmann; Juan Camilo Castro; Pablo Uribe; Pablo Zoroquiain; Cristian Navarrete-Dechent (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Skin cancer is the most frequent cancer worldwide and the most frequent periocular tumor. Keratinocyte Carcinomas (KC) located in periorificial areas, such as periocular tumors, are considered high-risk tumors. Mohs Micrographic Surgery (MMS) is considered the first line for the treatment of high-risk KC, providing a lower recurrence rate than conventional wide excision. Objective To describe the clinical-pathological features of periocular KC treated with MMS in a tertiary university center in Chile. Methods A single-center, retrospective study of patients with KC located on the periocular area, that underwent MMS between 2017‒2022. MMS details were recorded. Results One hundred thirteen patients with periocular carcinomas were included. The mean age was 59 ± 13 years; 52% were women. The most frequent location was the medial canthus (53%), followed by the lower eyelid (30.1%). The most frequent BCC histology was the nodular variant (59.3%). Regarding MMS, the average number of stages was 1.5 ± 0.7, and 54% of the cases required only 1 stage to achieve clear margins. To date, no recurrence has been reported. Tumors larger than 8.5 mm in largest diameter or 43.5 mm2 were more likely to require complex reconstruction. Study limitations Retrospective design and a relatively low number of patients in the SCC group. Possible selection bias, as larger or more complex cases, may have been referred to oculoplastic surgeons directly. Conclusion The present study confirms the role of MMS for the treatment of periocular KCs. Periocular KCs larger than 8.5 mm might require complex reconstruction. These results can be used to counsel patients during pre-surgical visits.